Subvertendo as regras do jogo político em 2018 e 2022: fake news como estratégias persuasivas em redes de desinformação pró Jair Bolsonaro - Gonçalves, Lucimar (2023)
Faced with the disturbing changes imposed by fake news in the contemporary political propaganda scenario, this research aimed to reflect on the persuasive tactics mobilized by such discursive pieces during the presidential campaigns of Jair Bolsonaro in 2018, and 2022, considering them highly relevant for the construction of speeches who subverted and continue to subvert the rules for contesting democratic elections. Considering the contextual differences between the two campaigns, the research examines the performative aspects of language in these rhetorical compositions from the point of view of advertising persuasion. Based on in-depth hermeneutics, we analyzed text, and images that addressed these discourses and aimed to mobilize the audience on social media, notably on WhatsApp. In this way, the study seeks to shed light on the persuasive strategies of fake news in political discourse that delegitimize the established channels of information and news circulation to constitute post-truth scenarios in alternative circuits of meaning production of an anti-democratic socio-communicational nature.